2021
DOI: 10.1128/spectrum.00284-21
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of New Trichophyton Members, T. persicum and T. spiraliforme spp. nov., as a Cause of Highly Inflammatory Tinea Cases in Iran and Czechia

Abstract: In this study, we describe two novel agents of dermatophytosis and summarize the clinical manifestation of infections. These new pathogens were discovered thanks to long-term molecular epidemiological studies conducted in Czechia and Iran. Zoonotic origins of the human infections are highly probable, but the animal hosts of these pathogens are poorly known. Further research is needed to refine our knowledge about these new pathogens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 84 publications
2
10
0
1
Order By: Relevance
“…Taxonomy and terms change and evolve rapidly in the field of mycology. [21][22][23][24] Trichophyton indotineae/Trichophyton mentagrophytes ITS genotype VIII, notwithstanding the terminological confusion, is no longer restricted to the Indian subcontinent. Its presence as early as between 2004 and 2013 has been documented in India, Australia, Iran and Oman.…”
Section: Trichophyton Mentagrophytes Genotype Viii/ Trichophyton Indo...mentioning
confidence: 99%
“…Taxonomy and terms change and evolve rapidly in the field of mycology. [21][22][23][24] Trichophyton indotineae/Trichophyton mentagrophytes ITS genotype VIII, notwithstanding the terminological confusion, is no longer restricted to the Indian subcontinent. Its presence as early as between 2004 and 2013 has been documented in India, Australia, Iran and Oman.…”
Section: Trichophyton Mentagrophytes Genotype Viii/ Trichophyton Indo...mentioning
confidence: 99%
“…The most important findings of the present study were new cases of isolation and identification of Trichophyton persicum. T. persicum is a new species in the T. benhamiae species complex that was recently discovered and described by Čmoková et al [ 18 ] Taghipour et al [ 19 ] have recently shown that some dermatophyte species/genotypes are associated with particular geographic areas and clinical manifestations. Until 2021, all 37 retrospectively identified strains were exclusively from seven different provinces in Iran and isolated from individuals with tinea corporis except one which was from an ectothrix tinea capitis case.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study by Ebrahimi et al [ 2 ] in Mashhad, using ITS gene location, 1.3% of dermatophyte isolates were reported as T. benhamiae while a reassessment of the isolate reveals its identity as T. persicum . Recently, Zareshahrabadi et al [ 20 ] also reported six cases of infection by T. benhamiae solely based on ITS sequencing, while more concentration on ITS sequences by Čmoková et al [ 18 ] showed that those isolates were T. persicum , in fact. It seems that most cases of isolates originated from Iran and those formerly reported as T. benhamiae senso stricto, were in fact T. persicum and the species is currently indigenous to Iran.…”
Section: Discussionmentioning
confidence: 99%
“…7 PCR products were sequenced using ITS5 and ITS4 primers 8 through a commercial service (Macrogen Europe). Using Mega 11 software (https://www.megas oftwa re.net/), ITS sequences were aligned with those of the species belonging to the T. benhamiae complex 3,9 deposited in GenBank (https://www.ncbi.nlm.nih.gov/ genba nk/), and a phylogenetic tree was constructed by the neighbour-joining analysis. The robustness of the branches was assessed by bootstrap analysis with 1,000 replicates.…”
Section: Case Descriptions and Methodologymentioning
confidence: 99%